2013
DOI: 10.1080/14719037.2012.757349
|View full text |Cite
|
Sign up to set email alerts
|

Towards Charity Accountability: Narrowing the gap between provision and needs?

Abstract: Although charities currently play a rich and varied role in modern society, their continued success is dependent upon the public's trust. With respect to charity accountability, two key questions emerge: to whom is a charity accountable; and what form should that account take? Despite the widespread acceptance that charities should discharge accountability, there is limited knowledge of the relative importance of different stakeholder groups and whether the information currently being disclosed meets their nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 26 publications
7
94
0
Order By: Relevance
“…Where ratios were provided, the authors commented that understanding of these figures was hindered by charities' failure to give explanations or comparatives. Connolly and Hyndman (2013), using a different methodology and wider definitions, identified that rates of disclosure of efficiency measures were higher than previous studies (although still very modest), with fewer than 25 per cent of charities disclosing an efficiency measure or conversion ratio in either their TAR or Annual Review [endnote 5]. These previous studies focussed on the extent of reporting, largely ignoring the manner of reporting (which is explored in this study).…”
Section: Evidence On Efficiency Reporting From Previous Studies Of Ukmentioning
confidence: 73%
See 4 more Smart Citations
“…Where ratios were provided, the authors commented that understanding of these figures was hindered by charities' failure to give explanations or comparatives. Connolly and Hyndman (2013), using a different methodology and wider definitions, identified that rates of disclosure of efficiency measures were higher than previous studies (although still very modest), with fewer than 25 per cent of charities disclosing an efficiency measure or conversion ratio in either their TAR or Annual Review [endnote 5]. These previous studies focussed on the extent of reporting, largely ignoring the manner of reporting (which is explored in this study).…”
Section: Evidence On Efficiency Reporting From Previous Studies Of Ukmentioning
confidence: 73%
“…Based on a strict definition, support costs and governance costs are quite different from administration costs; however, it is possible that many readers of reports would not be aware of that difference. Combining the proportions of charities disclosing administration, support and governance ratios (as was done by Connolly and Hyndman, 2013), a slightly greater proportion of charities are reporting these than in any previous study (including Connolly and Hyndman, 2013). The governance cost ratio was much more often disclosed than a support cost or administration cost ratio.…”
Section: Limited Reporting Of the Suggested Efficiency Measures And Cmentioning
confidence: 86%
See 3 more Smart Citations